Modified safe technique for circumcision - Nitin Mokal; Navadeep Chavan (Indian Journal of Plastic Surgery)
We have used surgical gauze under the prepuceal skin as a pack in 20 cases prior to marking incision for circumcision. The prepuceal adhesions were first dissected and seperated. The method allows a stable, well-supported prepuceal surface for marking incisions and avoids injuries to the glans. Because the prepuceal surface is taut and stable, hemostasis is easier and quicker and the operating time is reduced.